Novel nuclear barcode regions for the identification of flatfish species. (September 2017) - Paracchini, Valentina; Petrillo, Mauro; Lievens, Antoon; Puertas Gallardo, Antonio; Martinsohn, Jann Thorsten; Hofherr, Johann; Maquet, Alain; Silva, Ana Paula Barbosa; Kagkli, Dafni Maria; Querci, Maddalena; Patak, Alex; Angers-Loustau, Alexandre
Abstract: The development of an efficient seafood traceability framework is crucial for the management of sustainable fisheries and the monitoring of potential substitution fraud across the food chain. Recent studies have shown the potential of DNA barcoding methods in this framework, with most of the efforts focusing on using mitochondrial targets such as the cytochrome oxidase 1 and cytochrome b genes. In this article, we show the identification of novel targets in the nuclear genome, and their associated primers, to be used for the efficient identification of flatfishes of the Pleuronectidae family. In addition, different in silico methods are described to generate a dataset of barcode reference sequences from the ever-growing wealth of publicly available sequence information, replacing, where possible, labour-intensive laboratory work. The short amplicon lengths render the analysis of these new barcode target regions ideally suited to next-generation sequencing techniques, allowing characterisation of multiple fish species in mixed and processed samples. Their location in the nucleus also improves currently used methods by allowing the identification of hybrid individuals. Highlights: Fish product mislabelling remains a serious concern, in particular for the flatfishes. We identified new DNA barcode regions in the fish nuclear genome. The new barcodes allowed the identification of hybrid specimens. The new barcodes allowed the identification of multiple species in a processed sample.